Clinical outcomes and safety of neuromodulation in hemorrhagic stroke patients with a Glasgow Coma Scale above eight and non-operative lesions: Focusing on neurological recovery in the Thai context - Panu Boontoterm; Siraruj Sakoolnamarka; Karanarak Urasyanandana; Pusit Fuengfoo (World Neurosurgery: X)
Objectives: Hemorrhagic stroke leads to significant brain dysfunction and complex neurological sequelae, even with aggressive surgical interventions aimed at preventing secondary brain injury. However, alternative neuromodulation therapies may provide promising options. Cerebrolysin, a neuromodulation agent derived from pig brain tissue, possesses potential neuroprotective properties that could aid in the protection and repair of brain cells. This study aims to compare the efficacy and safety of Cerebrolysin against standard care in patients with hemorrhagic stroke who have a Glasgow Coma Scale greater than eight and non-operative lesions. Methods: In this randomized, single-blind study, participants were divided into two groups: one receiving Cerebrolysin (n = 32) and the other receiving usual care (n = 36). Outcomes were assessed at six months using the NIHSS, Barthel Index, and modified Rankin Scale. The study compared outcome measures and safety between the two groups. Results: The results showed that patients receiving Cerebrolysin had significantly lower NIHSS scores [6.40 ± 2.13 vs. 10.02 ± 3.75 (p = 0.013)] and modified Rankin Scale scores [3.13 ± 2.87 vs. 4.62 ± 1.38 (p = 0.047)] compared to those receiving usual care. Additionally, the Barthel Index was significantly higher in the Cerebrolysin group [77.23 ± 11.71 vs. 68.82 ± 9.63 (p = 0.025)]. Administration of Cerebrolysin was associated with no significant occurrences of seizures or cardiovascular complications. Conclusions: Cerebrolysin administration is associated with improved functional neurorecovery and a higher likelihood of favorable outcomes in patients with hemorrhagic stroke and a Glasgow Coma Scale greater than eight with non-operative lesions.